Gender and Age Effects on the Trajectory of Depression in Opioid Users during Methadone Maintenance Treatment - Wang, Peng-Wei; Lin, Huang-Chi; Yang, Yi-Hsin Connie; Hsu, Chih-Yao; Chung, Kuan-Sheng; Wu, Hung-Chi; Yen, Cheng-Fang (Frontiers in Psychiatry, 2017)
Introduction Both heroin use and depression are significant health problems. Methadone maintenance treatment (MMT) can be of great benefit to heroin users. However, changes in the level of depression in heroin users during MMT are not clear. Gender and age are also important factors in the development of depression, and whether gender and age moderate changes in depression in heroin users during MMT warrants further study. This study aimed to explore: 1) the trajectory of depression in opioid users during MMT, and 2) the moderating effects of gender and age on the trajectory of depression in opioid users receiving MMT. Method A total of 294 intravenous heroin users were recruited into this 9-month observational study. The level of depression was measured at the intake interview and at follow-up interviews every 3 months. A latent growth model was used to analyze the trajectory of the level of depression among the participants. Results Depression improved rapidly during the first 3 months of MMT and slowly after the first 3 months in both the female and male heroin users. There was no gender difference in the level of depression at each follow-up point. The level of depression in the female heroin users decreased faster than that in the male heroin users. In addition, the level of depression in the younger heroin users decreased faster than that in the older subjects. Conclusion Depression in female and younger heroin users improved more rapidly than in male and older subjects, respectively.